Growth/differentiation factor-15 is an abundant cytokine in human seminal plasma - Soucek, Karel; Slabáková, Eva; Ovesná, Petra; Malenovská, Alice; Kozubík, Alois; Hampl, Ales (Human reproduction (Oxford, England), 2010)
BACKGROUND: Transforming growth factor-β cytokines have various biological effects in female reproductive tissue, including modulation of inflammatory response and induction of immune tolerance to seminal antigens in the reproductive tract. However, no studies have analyzed the presence of growth/differentiation factor-15 (GDF-15/macrophage inhibitory cytokine-1) in seminal fluid or demonstrated the quantity and form of GDF-15, its possible role or the relationship between its concentration and semen quality. METHODS: The form and the concentration of GDF-15 were determined in 53 seminal plasma samples of both fertile and infertile men by ELISA and western blot. The sperm cells of three volunteers were treated with recombinant GDF-15, and cell viability and apoptosis were assessed by flow cytometry. The effect of GDF-15 on vaginal epithelial cells and peripheral blood mononuclear cells (PBMCs) was analyzed by quantitative RT-PCR. RESULTS: The GDF-15 concentration in seminal plasma ranged from 0.2 to 6.6 μg/ml as determined by ELISA. Western blot analysis revealed that GDF-15 is present in the active form. In vitro cultivation of sperm cells with GDF-15 did not affect their viability or rates of apoptosis; however, it did inhibit proliferation of PBMCs and induce expression of FOXP3 in CD4+CD25+ cells. CONCLUSIONS: To the best of our knowledge, this is the first demonstration that GDF-15 is an abundant cytokine in seminal plasma, although its concentration is not associated with semen quality or the fertility/infertility status of the donors. Moreover, our data show that GDF-15 displays immunosuppressive characteristics.
Keywords: dospělí; proliferace buněk; apoptóza; Female; Interleukin-2 Receptor alpha Subunit; spermie; Adult; Apoptosis; ženské pohlaví; Semen; růstový diferenciační faktor 15; Spermatozoa; Leukocytes, Mononuclear; lidé; Epithelial Cells; forkhead transkripční faktory; sperma; receptor interleukinu-2 - alfa-podjednotka; Humans; Middle Aged; Forkhead Transcription Factors; Semen Analysis; Male; Growth Differentiation Factor 15; analýza spermatu; Cell Proliferation; lidé středního věku; CD4-Positive T-Lymphocytes; Cell Survival; mužské pohlaví; viabilita buněk; epitelové buňky; leukocyty mononukleární; CD4-pozitivní T-lymfocyty